Pengaruh Pemberian Formula Enteral Diabetes Melitus Berbasis Tepung Labu Kuning (Cucurbita Moschata) Dan Tepung Ikan Lele (Clarias Gariepinus) Terhadap Kadar Gula Darah Pasien Diabetes Melitus Di Charitas Hospital Palembang - Chika Erian; Yuli Hartati; Yulianto Yulianto; Imelda Telisa (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2022)
Background: Diabetes mellitus is a degenerative disease caused by a lack of the hormone insulin, or the ineffectiveness of the body to use insulin which is indicated by the blood sugar level at ≥200 mg / dl. The manufacture of enteral formulas based on pumpkin flour and catfish meal is expected to be an alternative enteral food for people with diabetes mellitus.Purpose: The purpose of the study was to examine the effect of enteral diabetes mellitus formula based on pumpkin flour (cucurbitamoschata) and catfish meal (clariasgariepinus) on blood sugar levels in patients with diabetes mellitus at Charitas Hospital Palembang. Methods: This study useda pretest-posttest with two group research design. The number of samples of organoleptic test panelists as many as 30 people who were outpatient DM patients and 30 people each intervention sample for the treatment group and the comparison group were inpatients at Charitas Hospital Palembang Results:The results of data analysis using the dependent t-test showed that the average glucose levels before treatment in the treatment group were 192.24 mg/dl and 179.14 mg/dl in the comparison group. The average blood glucose after treatment in the treatment group was 177.61 mg/dl and in the comparison group was 190.02 mg/dl. Meanwhile, the independent sample t-test showed the difference in the average blood glucose level in the treatment group was 43.94 mg/dl and the comparison group was -13.86 mg/dl (p-value = 0.005). Conclusion:Administration of enteral DM formula based on pumpkin flour and catfish meal has an effect on blood glucose in DM patients.